2022
DOI: 10.4314/bcse.v36i3.11
|View full text |Cite
|
Sign up to set email alerts
|

Novel palladium(II) complex derived from mixed ligands of dithizone and triphenylphosphine synthesis, characterization, crystal structure, and DFT study

Abstract: ABSTRACT. A novel distorted square-planar palladium(II) complex of the type [Pd(Hdz)(PPh3)Cl], where (Hdz = dithizone mono deprotonate and PPh3 = triphenylphosphine), was synthesized in dichloromethane reactions between PdCl2 and a mixture of Hdz and PPh3. The new Pd(II) complex has been identified by FT-IR, electronic spectra, DFT calculations, molar conductivity, and single-crystal X-ray diffraction. An X-ray diffraction study revealed the structure of this complex, indicating distorted square planar coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…The method is rapid, sensitive, selective, and gives highly reproducible results. Computational calculations additionally helped in confirming the geometrical, electrical and thermodynamic aspects of the studied molecules including HMPB and its complex with Pd(II) in an analogy with the previously reported study over transition metal complexes [23,24]. Where, stability of the complex, intermolecular interactions and charge distribution inside the investigated molecules have been revealed by the FMO's values and MEP diagrams, the molecular docking studies assisted in analyzing the exact conformation of the molecule by finding the nature of interaction and binding process between ligands and active site proteins along with the location and proximity of the involved functional groups with highly supportive results, in accordance to the analytical findings.…”
Section: Introductionsupporting
confidence: 69%
“…The method is rapid, sensitive, selective, and gives highly reproducible results. Computational calculations additionally helped in confirming the geometrical, electrical and thermodynamic aspects of the studied molecules including HMPB and its complex with Pd(II) in an analogy with the previously reported study over transition metal complexes [23,24]. Where, stability of the complex, intermolecular interactions and charge distribution inside the investigated molecules have been revealed by the FMO's values and MEP diagrams, the molecular docking studies assisted in analyzing the exact conformation of the molecule by finding the nature of interaction and binding process between ligands and active site proteins along with the location and proximity of the involved functional groups with highly supportive results, in accordance to the analytical findings.…”
Section: Introductionsupporting
confidence: 69%
“…The overall electronic energy value of a synthesized bis amide is -34694.5 eV. The dipole moment is 10.4 Debye, E-HOMO), (E-LUMO) and (∆E) is -6.2254, -2.85093 and 3.37447 eV respectively, Negative values of E-HOMO) and (E-LUMO) it showed that the bis amide is thermodynamically stable [33,34], the HOMO orbitals are distributed over the amide group and toluidine moieties and LUMO orbitals are mainly distributed over meta-nitro phenyl moieties. In the MEP map the red area represents the electronegative region and the blue area represents the electropositive region C, and H lies in the blue region, where O and N lie in the red region [35].…”
Section: Dft Studymentioning
confidence: 93%
“…The ligands HL1 and HL2 showed three absorption bands between 214 and 231 nm, 273 nm, and 341 and 345 nm, respectively. These bands are assignable to the π → π* and n → π* transitions due to C--C and C--N, respectively [66]. After complexation, the bands showed a red shift toward absorption maxima at 232-245 nm and 290-291 nm, as well as a hypochromic effect.…”
Section: Uv-visible Absorption Studiesmentioning
confidence: 97%